2016
DOI: 10.1111/ina.12301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-volatile organic compounds, water-based paint on aggravation of allergic disease in schoolchildren

Abstract: Whether indoor painting aggravates preexisting allergic diseases remains unclear. We aimed to evaluate the impact of new classroom painting on aggravation of asthma, allergic rhinitis (AR), and atopic dermatitis (AD) in children. Studied school was previously painted with conventional water-based paint 20 years ago and had natural ventilation system. We identified a total of 172 children aged 10-12 years with allergic diseases in 17 classrooms, which were allocated to newly painted rooms with low-volatile orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Further studies are needed to confirm the effect of indoor pollutant exposure on chronic urticaria in cases of remodeling house or moving into another house and to assess the relationships of environmental pollutants and indoor chemicals with symptoms of urticaria. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to confirm the effect of indoor pollutant exposure on chronic urticaria in cases of remodeling house or moving into another house and to assess the relationships of environmental pollutants and indoor chemicals with symptoms of urticaria. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Indoor decorative materials have been repeatedly associated with the occurrence of respiratory diseases in children. 2 , 17 , 18 The results of this study showed that floor material, wall surface material, and carpet placement in a room were associated with otitis occurrence in children. It is presumed that newly purchased furniture and renovation materials in dwellings have some volatilization of chemical composition.…”
Section: Discussionmentioning
confidence: 72%
“…Emerging literature document that early exposure to indoor VOCs from renovation, furniture and other sources are associated with onset and persistence of asthma symptoms and symptom severity [21][22][23][24]. While respiratory health effects of VOCs have been subject to research scrutiny [6,25,26], this research makes a novel contribution by assessing the association of paint exposure with asthma attack among children. The findings of this research have health and policy implications for managing VOC exposure from paints.…”
Section: Discussionmentioning
confidence: 98%